Meningkatkan Hasil Belajar Passing Bawah Bola Voli melalui Bermain Melempar Bola - Deka Ismi Mori Saputra; Gusniar Gusniar (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2019)
The purpose of this study was to determine the application of playing throwing a ball to improve the learning of passing under volleyball for Class IV Elementary 85 / II Floating Mudik students. The study used a class action research design which was carried out in two cycles, each cycle consisting of planning, action implementation, observation and reflection. The subjects of this study were Class IV students, totaling 20 students. Volleyball learning outcomes data obtained through performance tests, observation sheets are used to collect data on student activities in following the volleyball learning process with the throwing ball method. The results of this study were obtained based on an assessment of three aspects, namely psychomotor, affective, and cognitive. The results of the study showed a significant improvement from cycle I to cycle II. The results of the assessment, in the first cycle 58.62% in the complete category the number of students who completed was 15 students. In cycle II there was an increase in students in the complete category by 82.76% with the number of students who completed was 18 students. Conclusion, playing throwing a ball can improve learning outcomes under volleyball passing Keywords: Learning Outcomes, Throwing the Ball, Passing Down